Institutions européennes, cartels de partis nationaux et développement des partis européens : que révelent les débats sur les reglements 2001 et 2003? - Erol Kulahci (Romanian Journal of European Affairs)
The relevance of supranational parties in the European political life represents an increasing concern among practitioners and researchers. Their attributed place represents an important aspect of that problem. Based upon the current literature, this article wants to proceed to an institutional analysis of the 2001 and 2003 Regulations focusing upon the debate regarding the statute, financing and functions of the European parties. We will prove that the European institutions have permitted considerable advances regarding the statute and financing while they have stopped the progress as regards the functions, for instance, of electoral representation. Finally, our analysis will permit us to evaluate the attitudes of various European institutional actors, to diversify and refine the thesis of « national parties’ cartel » and to confirm the importance of the problem of the deficit of partisan representation within the European Union.